Optimization of electromagnetic and hadronic extensive air shower identification using the muon detectors of the TAIGA experiment - Astapov, I; Bezyazeekov, P; Boreyko, V; Borodin, A; Brueckner, M; Budnev, N; Chiavassa, A; Dyachok, A; Fedorov, O; Gafarov, A; Garmash, A; Gorbunov, N; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
The TAIGA experiment in the Tunka valley near Lake Baikal is planning an extension with new TAIGA-Muon scintillation detector stations. The main purpose of TAIGA is gamma-ray astronomy in the TeV to PeV energy range and cosmic ray physics. The purpose of the Taiga-Muon detectors is to measure the muon component of air showers for improving cosmic ray composition measurements as well as gamma-hadron separation above 100 TeV. Monte Carlo simulations of the experiment are done with the software packages CORSIKA and GEANT4. Extensive air showers of primary particles in the energy range 100-3000 TeV are created with CORSIKA. The trigger efficiency is calculated and used for optimization. The suppression factor of hadronic showers versus electromagnetic showers is studied, leading to an optimum depth of soil absorber (2 m), at the lowest energy range. Data on the identification efficiency for primary gamma-quanta and proton events are presented as well as the suppression factor.